Виробництво зеленого амоніаку для зеленого вибору України - Volchyn I.A.; Rashchepkin , Vladyslav; Cherervatskyi, Danylo (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
Ukraine's Green Energy Transition by 2050 involves a number of energy transformations in the economy, including decarbonisation, fossil fuel abandonment and the further development of renewable energy sources (RES). For a long-term storage of energy generated by RES, the chemical systems are most suitable that convert electricity into chemical energy of such types of fuels like hydrogen and ammonia, which after being burnt do not produce emissions of carbon monoxide and oxide, sulfur dioxide, or dust. Ammonia manufacturers that use traditional production technology are being themselves large consumers of fossil fuels and electricity and emit hundreds of millions of tons of carbon dioxide. An ecological alternative is the synthesis of green ammonia based on the electrolytic production of hydrogen using electricity produced by RES. But this option requires a lot of electricity. In the context of Ukraine, with an annual demand for the production of 5 million tons of carbon-free ammonia, the required consumption of electricity amounts to 55 billion kWh. To obtain green ammonia in Ukraine, it is necessary to dramatically increase the scope of nuclear power plants and RES capacities, while abandoning the use of coal-fired power plants. Decentralized production of green ammonia can become an effective regulator of electric power in the power system without restrictions on the operation of nuclear power plants and RES. The start of this production will come after the development of synthesis technologies of green ammonia and the expiration of RES preferences in the energy market of Ukraine.